A tradução da tradição brasileira : a representação do Brasil em textos turísticos como fonte de construção identitária - Dalben, Tatiany Pertel Sabaini (2008)
This research investigates issues related to the building of identities and social practices that take place in the English foreign language classroom environment in Brazil . To achieve such an objective, a set of tourist texts related to the State of Espírito Santo, originally written in Portuguese and translated into English, made up the corpus in which we carried out contrastive analyses, relying on Translation Procedures. Themes related to translation processes, practices, and theories, intercultural studies and contrastive analysis were discussed and problematized, mainly through deconstructive and post-colonial perspectives. The objective of this research is to present data for the training of English teachers so as to demonstrate that, while considering a set of theoretical references, educators may present linguistic contents related to the language under study, as they participate in the building of the identities that occur as the result of the acquisition of knowledge within an interdisciplinary perspective.